Bioactive Compounds of Turmeric (Curcuma longa L.) - Oliveira Filho, Josemar Gon Ç Alves de [UNESP] (2020)
Curcuma longa, a native species to South Asia, is commonly known as turmeric and traditionally used as a spice and dye in culinary preparations and as a traditional herbal medicine. The bioactive compounds of C. longa have different effects such as antioxidant, antitumor, antimicrobial, insecticide, larvicide, repellent, anticancer, anti-inflammatory, healing, and gastroprotective properties. In this chapter, we describe the major chemical compounds present in C. longa and how these compounds demonstrate biological potential in human health. C. longa and its bioactive compounds have important health-promoting effects and have the potential for the development of pharmaceuticals, nutraceuticals, or food ingredients.